2012
DOI: 10.1111/j.1751-0813.2012.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

The feral horse foot. Part A: observational study of the effect of environment on the morphometrics of the feet of 100Australian feral horses

Abstract: The morphology of the feral horse foot appeared to be affected by the distance travelled and by the abrasive qualities and mechanical properties of the substrate under foot. There were marked differences in some conformation parameters between the feral horses in the current study and domestic horses in previous studies. Although the conformation of the feral horse foot may have some prescriptive value, concerns regarding abnormal foot anatomy warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
4
16
1
Order By: Relevance
“…The study group had a mix of the sexes (58 males, 42 females) and all subjects were at least 4 years of age, as assessed by dentition. The results of the detailed morphometric analysis of the same 100 feet, together with a detailed description of the horses and their habitats, are described elsewhere . DNA analysis of horse hair samples from four of the five populations in the current study confirmed that 93% of the genetic material was common to each population and there was no measurable difference in breed origin among the five populations…”
Section: Methodssupporting
confidence: 58%
See 3 more Smart Citations
“…The study group had a mix of the sexes (58 males, 42 females) and all subjects were at least 4 years of age, as assessed by dentition. The results of the detailed morphometric analysis of the same 100 feet, together with a detailed description of the horses and their habitats, are described elsewhere . DNA analysis of horse hair samples from four of the five populations in the current study confirmed that 93% of the genetic material was common to each population and there was no measurable difference in breed origin among the five populations…”
Section: Methodssupporting
confidence: 58%
“…The feet from the soft‐substrate, moderate‐travel horses (Cliffdale) did not have abnormal radiographic features. In the present study, the HWDPD of the Cliffdale population was significantly less (P < 0.05) than that of the horses from the hard‐substrate environments in our previous study and was within the normal range for sound domestic horses . There were no radiographic signs of laminitis in the Cliffdale (soft substrate) population.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Kobluc et al (1989) showed mean values between 50 and 54.6 degrees in 95 racehorses. Hampson et al (2013) found mean values of 52.8 ± 2.6 degrees for ferral horses, which are higher than the ones seen in this study.…”
Section: Figcontrasting
confidence: 56%